A companion to the Neronian age - Dinter, Martin T.; Buckley, Emma. (Chichester, West Sussex, U.K. : Wiley-Blackwell, 2013)
Provides an authoritative overview and helpful resource for students and scholars of Roman history and Latin literature during the reign of Nero. It offers an unusual breadth and range of material, including substantial treatments of politics, administration, the imperial court, art, archaeology, literature and reception studies.
Introduction: The Neronian (Literary) "Renaissance" / Martin T. Dinter -- Part I. Nero -- The Performing Prince / Elaine Fantham -- Biographies of Nero / Donna W. Hurley -- Nero the Imperial Misfit : Philhellenism in a Rich Man's World / Sigrid Mratschek -- Part II. The Empire -- The empire in the age of Nero / Myles Lavan -- Apollo in arms : Nero at the frontier / David Braund -- Domus Neroniana : The Imperial Household in the Age of Nero / Michael J. Mordine -- Religion / Darja Eterbenc Erker -- Neronian Philosophy / Jenny Bryan -- Part III. Literature, Art and Architecture -- Seneca, Apocolocyntosis / Christopher L. Whitton -- The Carmina Einsidlensia and Calpurnius Siculus' Eclogues / John Henderson -- Seneca's Philosophical Writings : Naturales Quaestiones, Dialogi, Epistulae Morales / Jonathan Mannering -- Senecan Tragedy / Emma Buckley -- Lucan's Bellum Ciuile / Philip Hardie -- Petronius' Satyrica / Tom Murgatroyd -- Persius / Marden Fitzpatrick Nichols -- Columella, De Re Rustica / Christiane Reitz -- Literature of the World : Seneca's Natural Questions and Pliny's Natural History / Aude Doody -- Greek Literature Under Nero / Dirk Uwe Hansen -- Buildings of an Emperor : how Nero transformed Rome / Heinz-Jürgen Beste and Henner von Hesberg -- Portraits of an Emperor : Nero and the Sun / Marianne Bergmann -- Neronian Wall-Painting : A Matter of Perspective / Katharina Lorenz -- Part IV. Reception -- Nero in Jewish and Christian Tradition from the First Century to the Reformation / Harry O. Maier -- Haec monstra edidit : Translating Lucan in the early seventeenth century / Yanick Maes -- Haunted by Horror : The Ghost of Seneca in Renaissance Drama / Susanna Braund -- "Fantasies so varied and bizarre" : The Domus Aurea, the Renaissance, and the "grotesque" / Michael Squire -- Epilogue -- Nachwort: Nero from Zero to Hero / Miriam Griffin.
Includes bibliographical references and index.
Keywords: Nero, -- Emperor of Rome, -- 37-68.; Nero, -- 37-68 -- Emperor of Rome; Nero, -- Emperor of Rome, -- 37-68.; 54-68; Latin literature -- History and criticism; Art, Roman -- History; Architecture, Roman -- History; HISTORY -- Ancient -- Rome; Architecture, Roman; Art, Roman; Intellectual life; Latin literature; Rome -- History -- Nero, 54-68.; Rome -- Intellectual life; Rome (Empire); Electronic books; Criticism, interpretation, etc; History